2013
DOI: 10.1074/jbc.m113.477745
|View full text |Cite
|
Sign up to set email alerts
|

Gremlin-1 Is an Inhibitor of Macrophage Migration Inhibitory Factor and Attenuates Atherosclerotic Plaque Growth in ApoE−/− Mice

Abstract: Results:Gremlin-1 binds with high affinity to macrophage migration inhibitory factor and attenuates the progression of atherosclerosis. Conclusion:We describe a novel mechanism that regulates foam cell formation and plaque growth. Significance: The findings disclose a new mechanism for the regulation of plaque growth and may open novel therapeutic strategies to control the progression of atherosclerosis.Monocyte infiltration and macrophage formation are pivotal steps in atherosclerosis and plaque vulnerability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
75
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(76 citation statements)
references
References 57 publications
1
75
0
Order By: Relevance
“…54 Indeed, gremlin haplodeficiency reduces vascular remodeling in hypoxic lung and diabetes mellitus-associated kidney damage. 55 However, gremlin attenuates atherosclerotic plaque growth in ApoE − / − mice 56 and may act as neuroprotective factor for dopamine neuron degeneration. 57 Thus, the biological impact of gremlin downregulation or of its overexpression in different pathological settings seems to be strictly contextual.…”
Section: Discussionmentioning
confidence: 99%
“…54 Indeed, gremlin haplodeficiency reduces vascular remodeling in hypoxic lung and diabetes mellitus-associated kidney damage. 55 However, gremlin attenuates atherosclerotic plaque growth in ApoE − / − mice 56 and may act as neuroprotective factor for dopamine neuron degeneration. 57 Thus, the biological impact of gremlin downregulation or of its overexpression in different pathological settings seems to be strictly contextual.…”
Section: Discussionmentioning
confidence: 99%
“…28 Recently, the structural requirements of MIF to bind to CXCR2 were addressed, and it was revealed that MIF-chemokine receptor interactions are dependent on a pseudo-(E)LR motif and an N-loop-based 2-site binding mechanisms, typical for bona fide chemokines. 48,49 Notably, Gremlin-1 was recently identified as an endogenous inhibitor of MIF, and administration of a recombinant fusion molecule mGremlin-1-Fc that binds to MIF substantially reduced atherosclerotic lesion formation, 50 indicating its potential as a novel therapeutic strategy to limit atheroprogression.…”
Section: Chemokine-like Functions Of Migration Inhibitory Factormentioning
confidence: 99%
“…74 Moreover, the MIF inhibitor Gremlin-1 was shown to reduce atherosclerotic lesion formation. 50 Although a large number of molecules targeting chemokines and chemokine receptors including neutralizing antibodies for inflammatory diseases are currently in clinical trials, only few molecules targeting chemokines and their receptors have been approved by the US Food and Drug Administration. 75,76 In 2007, the CCR5 inhibitor maraviroc (for prevention of HIV) was approved; the CXCR4 antagonist mozobil (for hematopoietic stem cell mobilization) was approved in 2008.…”
Section: Antichemokine Drugs: Future Challengesmentioning
confidence: 99%
“…[11][12][13][14][15] Because most of these diseases are ameliorated by either genetic deletion of Mif or MIF neutralization, anti-MIF therapies have raised significant clinical interest. MIF levels in plasma are enhanced in patients with acute myocardial infarction and associated with inflammatory markers C-reactive protein and IL-6 and correlate with cardiac necrosis marker troponin I release.…”
Section: Circulation Researchmentioning
confidence: 99%